Self-Configurable Current-Mirror Technique for Parallel RGB Light-Emitting Diodes (LEDs) Strings - Durrani, Shaheer Shaida; Nawaz, Asif; Shahzad, Muhamamd; Najam, Zeeshan; Khan, Rehan Ali; Abu Zaharin, Ahmad; Shah, Ahmed Ali; Ahmed, Sheeraz (The Science and Information (SAI) Organization Limited, 2020)
Traditional current-mirror circuits require buck converter to deal with one fixed current load. This paper deals with improved self-adjustable current-mirror methods that can address different LED loads under different conditions with the help of one buck converter. The operating principle revolves around a dynamic and self-configurable combinational circuit of transistor and op-amp based current balancing circuit, along with their op-amp based dimming circuits. The proposed circuit guarantees uniformity in the outputs of the circuit. This scheme of current-balancing circuits omitted the need for separate power supply to control the load currents through different kinds of LEDs, i.e. RGB LEDs. The proposed methods are identical and modular, which can be scaled to any number of parallel current sources. The principle methodology has been successfully tested in Simulink environment to verify the current balancing of parallel LED strings.